Combination of Lactobacillus plantarum improves the effects of tacrolimus on colitis in a mouse model - Lv, Wei; Zhang, Di; He, Tian; Liu, Yingying; Shao, Limei; Lv, Zhongping; Pu, Xiaoping; Wang, Yufang; Liu, Ling (Frontiers in Cellular and Infection Microbiology, 2023)
The gut microbiome has been considered to play an important role in inflammatory bowel disease (IBD). Our previous study reported that tacrolimus-altered gut microbiota elicited immunoregulatory effects in both colonic mucosa and circulation, contributing to an increased allograft survival rate in mice. Here, we aimed to observe the changes in the tacrolimus-induced microbiome in a dextran sulfate sodium (DSS)-induced colitis mouse model and explore the possibility and efficacy of combination therapy with tacrolimus and the microbiome on colitis. Mice were divided into the control, DSS, tacrolimus monotherapy and tacrolimus plus Lactobacillus plantarum 550 (Lacto)-treated groups. The body weight, stool consistency, hematochezia and survival of mice were observed daily. Total RNA from colonic mucosa was extracted and subjected to transcriptome sequencing. Cecal contents were collected and the 16S rRNA sequencing was performed to characterize the gut microbiome and the ultrahigh- performance liquid chromatography-MS/MS (UHPLC-MS/MS) was used for targeted quantification of bile acids. The results confirmed that tacrolimus significantly ameliorated DSS-induced colitis in mice. Beneficial alterations of the gut microbiome characterized by a remarkable expansion of the genus Lactobacillus were induced by tacrolimus treatment. Oral supplementation with Lacto further improved the tacrolimus-mediated suppression of body weight loss in colitis, while the survival time of mice was further prolonged and the inflammation of colonic mucosa was obviously relieved. The immune and inflammation-related signaling pathways, including IFN-γ and IFN-α response, allograft rejection, IL2 STAT5 signaling and the inflammatory response pathways, were further downregulated in the tacrolimus plus Lacto cotreatment group. Cotreatment also improved the diversity of the gut microbiome and rescued the concentration of taurochenodeoxycholic acid (TCDCA) in colitis. The latter was positively correlated with the abundance of Lactobacillus but negatively related to the disease activity index score. Overall, our results indicated that Lactobacillus plantarum promoted the therapeutic effect of tacrolimus in experimental colitis, offering a promising strategy to combine tacrolimus and Lactobacillus in the treatment of colitis patients.